Facilitated Dissociation Kinetics of Dimeric Nucleoid-Associated Proteins Follow a Universal Curve - Dahlke, Katelyn (Biophys J, 2017)
Recent experimental work has demonstrated facilitated dissociation of certain nucleoid-associated proteins that exhibit an unbinding rate that depends on the concentration of freely diffusing proteins or DNA in solution. This concentration dependence arises due to binding competition with these other proteins or DNA. The identity of the binding competitor leads to different qualitative trends, motivating an investigation to understand observed differences in facilitated dissociation. We use a coarse-grained simulation that takes into account the dimeric nature of many nucleoid-associated proteins by allowing an intermediate binding state. The addition of this partially bound state allows the protein to be unbound, partially bound, or fully bound to a DNA strand, leaving opportunities for other molecules in solution to participate in the unbinding mechanism. Previous models postulated symmetric binding energies for each state of the coarse-grained protein corresponding to the symmetry of the dimeric protein; this model relaxes this assumption by assigning different energies for the different steps in the unbinding process. Allowing different unbinding energies not only has equilibrium effects on the system, but kinetic effects as well. We were able to reproduce the unbinding trends seen experimentally for both DNA and protein competitors. All trends collapse to a universal curve regardless of the unbinding energies used or the identity of the dissociation facilitator, suggesting that facilitated dissociation can be described with a single set of scaling parameters that are related to the energy landscape and geometric nature of the competitors.